Brief Report: Prevalence of Posttreatment Controller Phenotype Is Rare in HIV-Infected Persons After Stopping Antiretroviral Therapy. (1st July 2017) - Perkins, Matthew J.; Bradley, William P.; Lalani, Tahaniyat; Agan, Brian K.; Whitman, Timothy J.; Ferguson, Tomas M.; Okulicz, Jason F.; Ganesan, Anuradha
Abstract : Background: Posttreatment control of HIV infection is a rare phenomenon primarily described among those initiating treatment with antiretroviral therapy (ART) during early/acute HIV infection. Methods: We examined a large, well-characterized cohort of HIV-infected Department of Defense beneficiaries for the presence of posttreatment controllers (PTCs) whom we defined as individuals with sustained viral suppression for ≥6 months after discontinuation of ART. We defined those who became viremic within 6 months of discontinuing ART as rapid viremics (RVs) and compared demographic and clinical characteristics, CD4 counts, and viral loads prior, during, and after ART discontinuation between the 2 groups. Results: From a cohort of 6070 patients, we identified 95 who had been treated with ART for 2 years or more who subsequently discontinued ART and had viral load assessments available after discontinuation. Four (4.2%) of these 95 met our definition of PTC. The duration of viral suppression off of ART ranged from 267 to 1058 days with 1 of the 4 restarting ART without having redeveloped a significant viremia. All 4 patients initiated ART during chronic HIV infection. Demographic and clinical characteristics of PTCs were similar to RVs. Conclusions: While posttreatment control has predominantly been described among individuals who initiated ART in early/acute HIV infection, we identified 4 PTCs who started ART during chronic infection suggesting that posttreatment control also occurs among such patients. The rarity of PTCs identified in our cohort is consistent with reports from previous studies. Abstract : Supplemental Digital Content is Available in the Text.